2021
DOI: 10.3390/ijms22137149
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix-Associated Autologous Chondrocyte Implantation with Spheroids in the Treatment of Large Chondral Defects in the Knee: A Systematic Review

Abstract: Autologous chondrocyte implantation (ACI) is a cell therapy for the treatment of focal cartilage defects. The ACI product that is currently approved for use in the European Union (EU) consists of spheroids of autologous matrix-associated chondrocytes. These spheroids are spherical aggregates of ex vivo expanded human autologous chondrocytes and their self-synthesized extracellular matrix. The aim is to provide an overview of the preclinical and nonclinical studies that have been performed to ensure reproducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
0
17
0
3
Order By: Relevance
“…The intrinsic ability of spheroids to rapidly fuse with target tissue is believed to be crucial for regeneration [ 160 ]. In order to prevent their extrusion from NP, the adhesion of spheroids and migration of surface cells into NP, followed by spheroid remodeling, must take place.…”
Section: Spheroid-based Cell Therapies For Degenerative Disc Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic ability of spheroids to rapidly fuse with target tissue is believed to be crucial for regeneration [ 160 ]. In order to prevent their extrusion from NP, the adhesion of spheroids and migration of surface cells into NP, followed by spheroid remodeling, must take place.…”
Section: Spheroid-based Cell Therapies For Degenerative Disc Diseasementioning
confidence: 99%
“…3D configuration and increased paracrine effects of spheroids (compared to 2D) are thought to enhance the differentiation potential of therapeutic cells. The ability of spheroids to synthesize their own ECM results in the encapsulation of cells in native ECM, the composition of which is driven by the original cell type and culture conditions [ 87 , 160 ]. In the clinical repair of cartilage defects in the knee, AC-based spheroids (Spherox) generated a hyaline-like structure and showed the potential to synthesize an articular cartilage-specific matrix [ 22 , 112 ].…”
Section: Spheroid-based Cell Therapies For Degenerative Disc Diseasementioning
confidence: 99%
“…Moreover, in the course of this method, primary chondrocytes are first isolated and then cultured on polystyrene (i.e., in two-dimensional conditions), which leads to their dedifferentiation towards fibroblast-like cells. It was demonstrated that such cells possess limited ability to regenerate hyaline articular cartilage [ 6 , 7 , 8 , 9 , 10 , 11 ]. In the case of large-area lesions, there is a need to use grafts which will replace the fragments of missing tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Although autografts are considered as a “gold standard” in regeneration of cartilage defects, their availability is highly limited. For these reasons, current medical interest focuses on synthetic biomaterials, which not only have a composition and a structure similar to those of natural tissue, but also exhibit similar physicochemical, mechanical, and biological properties [ 6 , 7 , 8 , 9 , 10 , 11 ]. The biomaterials may be implanted directly without cells or in combination with cells; this constitutes a modern therapeutic strategy called matrix-associated autologous chondrocyte transplantation (MACT) [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hernigou et al [41] performed autologous mesenchymal stem cells implantation with aspiration and concentration of the iliac crest bone marrow. For talus chondral defect or ankle osteoarthritis, scaffolds, subchondral, or intra-articular injections of fresh autologous bone marrow concentrate, regenerative cells are possible as for the knee [42]; autologous chondrocyte implantation with spheroids in the treatment of significant chondral defects are another possibility [43] for the future.…”
mentioning
confidence: 99%